(untitled) (Per Musi, 2021)
This work focuses on a social debate raised in the mid-1980s by both American journalists and music critics regarding two of Prince’s records. The first, Around the World in A Day, was released in 1985; the second, Parade: Music from the Motion Picture Under The Cherry Moon, was released in 1986. The debate surrounding these records stemmed from assumptions that they referenced albums produced by The Beatles in the late 1960s. This article presents an inquiry on the relationship between Prince, journalists and music critics, as well as on the roles played by these and other social agents in the collective construction of meanings for these Prince’s records, including musicians who collaborated in their production.